The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11306-007-0093-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling by ion mobility mass spectrometry (IMMS)

Abstract: Ion Mobility Mass Spectrometry (IMMS) was evaluated as an analytical method for metabolic profiling. The specific instrument used in these studies was a direct infusion (DI)-electrospray ionization (ESI)-ambient pressure ion mobility spectrometer (APIMS) coupled to a timeof-flight mass spectrometer (TOFMS). The addition of an ion mobility spectrometer to a mass spectrometer had several advantages over direct infusion electrospray mass spectrometry alone. This tandem instrument (ESI-IMMS) added a rapid separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 36 publications
3
99
0
Order By: Relevance
“…Metabolites identified in biological samples like blood plasma are often linked with disease state and require methods for identification and quantification. Metabolomics analysis by IM-MS was first investigated with direct infusion (60 ), and more recently was coupled with LC as a rapid method to analyze the human blood metabolome, allowing identification of nearly 1100 metabolites, including 300 isomers (61 ). This methodology is especially useful in identification of low-abundance compounds that can be differentiated from background noise on the basis of their mobilities.…”
Section: Ims As a Tool For Improving Metabolomics Studiesmentioning
confidence: 99%
“…Metabolites identified in biological samples like blood plasma are often linked with disease state and require methods for identification and quantification. Metabolomics analysis by IM-MS was first investigated with direct infusion (60 ), and more recently was coupled with LC as a rapid method to analyze the human blood metabolome, allowing identification of nearly 1100 metabolites, including 300 isomers (61 ). This methodology is especially useful in identification of low-abundance compounds that can be differentiated from background noise on the basis of their mobilities.…”
Section: Ims As a Tool For Improving Metabolomics Studiesmentioning
confidence: 99%
“…Together it becomes a power analytical tool for identifying molecular structure and separating complex samples which MS alone might not be able to distinguish. Studies have found the resolving power of IMMS to be in the region of which is similar to capillary gas chromatography (18 For increased accuracy, PMT-MS is usually coupled with GC to provide additional separation (20).…”
Section: Techniques For Breath Testingmentioning
confidence: 99%
“…Among the various pulse sequence programs, 1 H-NMR has been routinely employed for high-throughput metabolomic studies due to its relatively short acquisition time per analysis. Alternatively, several conventional as well as innovative analytical instruments, such as Fourier transform infrared spectrometry [51], direct-infusion time-of-flight (TOF) MS [24,77], ion mobility MS [25], and LC-FT-ICR MS [48,91], have recently been applied to metabolomic studies.…”
Section: Analytical Technologiesmentioning
confidence: 99%